A4 - Dahlstedt,Elin (2025)
My project began with conversations about accessible design. In one discussion, someone mentioned that her mother couldn’t use public seating because it was too low. This made me question why such essential furniture is often inaccessible to those who need it most. Motivated by this, I set out to design a seating solution focusing on universal design principles. I contacted my former Universal Design teacher, Per-Olof Hedvall, who invited me to join his research project, Jämlikhetens Syntax. He has supported and guided me throughout the process. Together, we agreed that aesthetics, an often overlooked aspect of universal design, would also be a key focus of my work. I chose Skissernas Museum in Lund as the setting for the project. The museum emphasizes the creative process behind artworks, displaying numerous sketches and prototypes. Inspired by this, I folded two A4 sheets into a seating furniture piece to represent the many sketch papers found inside the museum. The final result is a modular, two-piece seating design that functions both as furniture and sculptural art, offering flexibility and accessibility without compromising visual expression.